“…They were just treating her Symptom by Symptom”: maternal experiences of having a child with spinal muscular atrophy in Ghana - Esther Doe-Yo Tawiah; Jacob Owusu Sarfo (BMC Palliative Care)
Abstract Background Children with Spinal Muscular Atrophy (SMA) face the challenges of a rare condition impacting their motor neurons, placing substantial caregiving burdens on their mothers. Despite being primary caregivers, mothers of children with SMA in Ghana often find their voices unheard, with restricted access to vital interventions like counselling, support groups, and respite care designed to aid them. This study aimed to explore the experiences of mothers caring for children with SMA in Ghana, where the diagnosis is often delayed and support systems are limited. Methods We conducted an interpretative phenomenological study with a purposive sample of seven mothers whose children, aged between 8 and 24 months, were diagnosed with Spinal Muscular Atrophy (SMA) and registered with the Rare Disease Ghana Initiative (RDGI). Individual interviews were conducted between August and September 2023 using semi-structured interview guides. The data were manually analysed using a pen-and-paper method. The study adhered to ethical guidelines, including informed consent procedures and confidentiality measures to protect participants’ rights and privacy. Results This study explored mothers’ experiences caring for children with SMA, revealing a spectrum of challenges that impact their physical, emotional, spiritual, and social well-being. The findings identified five dominant themes and thirteen subcategories, encompassing issues such as sleep deprivation, mental health concerns, emotional turmoil, practical difficulties, and social isolation. It was also found that mothers tend to have a deep connection to their faith and a sense of closeness to God during challenging times, which provides them with strength and comfort. This collectively identifies the difficult journey of these mothers as they seek diagnosis and treatment for their children. Conclusion The study identified challenges faced by mothers in caring for their children with SMA. These challenges are reported to significantly impact their physical, psychological, social, and spiritual well-being. To support these mothers effectively, it is recommended that the Ministry of Health, Ghana Health Service, healthcare professionals, policymakers, and non-governmental organisations in Ghana should consider community engagement and education, integration of spiritual care, and psychosocial support programmes.